Polyionic liquid modified polyamide material and preparation method thereof

High-temperature polyamide materials modified with polyionic liquid synergists have solved the problem of flame retardant precipitation, achieving a V0-level flame retardant effect with high gloss and high chemical resistance, making them suitable for new energy vehicle components.

CN121379140APending Publication Date: 2026-01-23EMS-GRIVORY (SU ZHOU) ENG PLASTICS CO LTD

Patent Information

Application Number
CN202511567608.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-10-30
Publication Date
2026-01-23

AI Technical Summary

Technical Problem

Existing high-temperature polyamide materials are prone to flame retardant precipitation during processing, which leads to a decrease in mechanical properties and fails to meet the requirements of high-temperature chemical resistance and halogen-free flame retardancy. Furthermore, traditional flame retardants are not suitable for the extrusion processing of high-temperature nylon.

Method used

By combining polyionic liquid synergists with high-temperature polyamide materials and adjusting the cationic and anionic structures to introduce specific functional groups, a novel flame-retardant system is formed, which reduces phase separation and small molecule precipitation, and improves material compatibility and mechanical properties.

Benefits of technology

It achieves high gloss and excellent chemical resistance in low-exudation V0 flame-retardant high-temperature polyamide materials, meeting the UL 94 0.4 mm~3.2 mm V0 flame-retardant requirements, while maintaining the tensile strength and elongation at break of the material, making it suitable for key components of new energy vehicles.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention relates to a polyion liquid modified polyamide material and a preparation method thereof. The polyamide material provided by the invention comprises a polyionic liquid synergist which comprises an ionic liquid polymer with a synergistic flame-retardant function and specifically comprises one or more of the following components: quaternary ammonium type dihydric phosphate polyionic liquid, imidazole type dihydric phosphate polyionic liquid and pyridine type dihydric phosphate polyionic liquid. The polyamide material provided by the invention can realize excellent flame retardant property, significantly reduce precipitation of the flame retardant and maintain excellent mechanical properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of polymer materials, specifically to low-V0 flame-retardant high-temperature polyamide materials and their preparation methods, and more particularly to polyionic liquid-modified low-V0 flame-retardant high-temperature polyamide materials and their preparation methods. Background Technology

[0002] High-temperature polyamide, also known as high-temperature nylon, is a linear thermoplastic engineering plastic with repeating aromatic amide groups in its molecular backbone. As one of the five major engineering plastics, polyamide possesses numerous excellent properties: high crystallinity, wear resistance, self-lubrication, heat resistance, and good electrical insulation. High-temperature polyamide is widely used in the manufacture of various mechanical parts, automotive components, electronic product housings, medical devices, and medical supplies. With the rise of new energy vehicles and the trend towards automotive electrification, it is particularly important that core battery, electric drive, and electronic control systems require polyamide materials with chemical resistance, excellent electrical insulation, and halogen-free flame retardancy. Developing multifunctional and diverse flame-retardant systems has become a top priority for the future development of flame-retardant nylon materials, among which the development of V0 flame-retardant reinforced high-temperature polyamide materials with low flame retardant release is urgently needed. This material needs to meet excellent halogen-free flame retardant properties from 0.4mm to 3.2mm. The polyionic liquid modified low-emission V0 flame retardant material of the present invention has halogen-free V0 flame retardancy, excellent insulation performance with CTI (relative tracking index) of 600V (PLC: 0), and good chemical resistance (oil resistance and coolant resistance). The low emission of flame retardant meets the requirements for high surface finish of the product.

[0003] Chinese invention patent application CN202211509001.X describes a low-fouling, halogen-free, flame-retardant reinforced nylon material, its preparation method, and its application. This invention uses Fischer-Tropsch wax to reduce melt viscosity, thereby reducing the degradation of flame retardants during processing and thus reducing mold fouling in the later stages of injection molding. However, the decrease in melt viscosity carries the risk of degradation in the material's mechanical properties, such as tensile strength and impact strength, failing to meet the requirements for high-temperature chemical resistance. Furthermore, Fischer-Tropsch wax is unsuitable for high-temperature nylon extrusion processing due to its tendency to decompose. Therefore, there is an urgent need to develop a low-exudation V0 flame-retardant high-temperature polyamide material.

[0004] This invention utilizes a novel polyionic liquid synergist that combines the functionality of an ionic liquid as a green solvent with the processing stability of a polymer. The green solvent characteristics include: a) low volatility, near-zero VOCs (volatile organic compounds), conforming to green chemistry principles; b) high thermal and chemical stability; and c) recyclability, reducing environmental pollution. The polyionic liquid synergist offers advantages in structural designability, for example: a) by adjusting the cationic form (quaternary ammonium salts, imidazoles, pyridines, etc.); b) by designing anionic forms (PF6). -(a) Phosphates, sulfonates); and c) Precisely customized polyionic liquid synergists by introducing specific functional groups (flame retardant groups, hydrophobic segments, alkyl segments, etc.) through copolymerization or graft modification. Preferably, the advantages of polyionic liquid synergists include, but are not limited to, the following: a) Polarity matching high-temperature polyamides can improve the compatibility of modified polyamide systems. They possess a special "intermolecular crosslinking" effect, which can be compounded with traditional nitrogen and phosphorus flame retardants to form a new flame retardant system. At the same time, it reduces the phase separation effect of the entire formulation system, reduces the amount of traditional flame retardants, and thus reduces the risk of small molecule flame retardant precipitation, achieving the 0.4mm~3.2mm V0 flame retardant requirement; b) The unique polymer structure of polyionic liquids can anchor the precipitation risk of small molecule flame retardants, reducing the accumulation of mold fouling after material injection molding; c) By adjusting the alkyl chain length, the mechanical properties of the material can be improved. Summary of the Invention

[0005] To address the shortcomings of existing technologies, one objective of this invention is to provide a low-emission V0 flame-retardant high-temperature polyamide material modified with polyionic liquid and its preparation method.

[0006] To achieve the above objectives, the present invention provides a polyamide material modified with a polyionic liquid and a method for preparing the same, wherein one or more polyionic liquid synergists selected from quaternary ammonium dihydrogen phosphate polyionic liquids, imidazole dihydrogen phosphate polyionic liquids, and pyridine dihydrogen phosphate polyionic liquids are used.

[0007] One aspect of the present invention provides a polyionic liquid-modified polyamide material, comprising, based on a total of 100 parts by weight, the following components in parts by weight:

[0008] 35-60 parts of polyamide

[0009] 20-50 parts chopped glass fiber

[0010] 10-30 parts flame retardant

[0011] Polyionic liquid synergist 0.1-2 parts

[0012] Antioxidant 0.1 to 1 part

[0013] Light stabilizer 0.1 to 1 part

[0014] Lubricant 0.1 to 0.5 parts

[0015] 1-5 parts of coloring masterbatch

[0016] The polyionic liquid synergist includes one or more of the following: quaternary ammonium dihydrogen phosphate polyionic liquid, imidazole dihydrogen phosphate polyionic liquid, and pyridine dihydrogen phosphate polyionic liquid.

[0017] The polyamide may include one or more of PA6T / 66, PA6T / 8T / 66, PA6I / 6T, PA6T / 6I, PA9T, and PA10T, wherein the Ubbelohde relative viscosity of the polyamide, using concentrated sulfuric acid as the test solvent, is 120–140 cm⁻¹. 3 / g.

[0018] The length of chopped glass fibers can be 3.0–4.5 mm, and the diameter can be 11–17 μm. The cross-section can be circular and / or elliptical. The ratio of the shorter to longer diameter in the elliptical cross-section can be 1:3 to 1:5.

[0019] Flame retardants may include those selected from flame retardant Exollt. ® OP1230 and flame retardant Exollt ® One or more of OP1400.

[0020] Quaternary ammonium dihydrogen phosphate polyionic liquids can be formed from quaternary ammonium dihydrogen phosphate monomers of formula a below:

[0021] Formula a

[0022]

[0023] Wherein, R1 can be an alkyl group, and R2 can be an alkylene group. Preferably, R2 can be ethylene, n-butylene, or n-hexylene.

[0024] Imidazole-type dihydrogen phosphate polyionic liquids can be formed from imidazole-type dihydrogen phosphate monomers of formula b below:

[0025] Formula b

[0026]

[0027] R3 can be an alkyl group, and R4 can be an alkylene group. Preferably, R4 can be ethylene, n-butylene, or n-hexylene.

[0028] Pyridine-type dihydrogen phosphate polyionic liquids can be formed from pyridine-type dihydrogen phosphate monomers of formula c below:

[0029] Formula c

[0030]

[0031] R5 can be an alkylene group. Preferably, R5 can be ethylene, n-butylene, or n-hexylene.

[0032] The antioxidant may include one or more selected from hindered phenolic antioxidants and phosphite antioxidants, wherein the hindered phenolic antioxidants may include one or more selected from N,N'-hexamethylene bis(3,5-di-tert-butyl-4-hydroxyphenylpropionamide) and pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate]; and the phosphite antioxidants may include one or more selected from bis(2,4-dicumylphenyl)pentaerythritol diphosphite and tris(2,4-di-tert-butylphenyl) phosphite.

[0033] The light stabilizer may include one or more selected from N,N'-bis(2,2,6,6-tetramethyl-4-piperidinyl)-N,N'-dialdehyde hexamethylenediamine and bis(2,2,6,6-tetramethyl-4-piperidinyl) sebacate.

[0034] The lubricant may include one or more selected from polymeric ionic liquid complexes and stearates, wherein the stearates may include one or more selected from calcium stearate, magnesium stearate and zinc stearate.

[0035] Coloring masterbatch may include one or more of carbon black masterbatch and orange masterbatch.

[0036] Polyamide materials can achieve a UL94 flame retardancy rating of V0 for thicknesses from 0.4 mm to 3.2 mm. During aging tests at 23–85°C and 50–85% relative humidity for 1000 hours, the amount of flame retardant released (expressed as phosphorus weight fraction) can be below 0.25 wt%. Polyamide materials retain over 85% of their tensile strength and over 90% of their elongation at break in ethylene glycol aqueous solution at 130°C for 3000 hours. Furthermore, polyamide materials retain over 95% of their tensile strength, over 90% of their elongation at break, and 100% of their CTI (Continuous Transmission Tier) under aging conditions in transmission fluid at 150°C and 504 hours.

[0037] Another aspect of the present invention provides a method for preparing a polyamide material modified by a polyionic liquid, comprising the following steps:

[0038] Step 1, Prepare raw materials: The raw materials consist of the following components in parts by weight based on a total of 100 parts by weight:

[0039] 35-60 parts of polyamide

[0040] 25-50 parts of chopped glass fiber

[0041] 10-20 parts flame retardant

[0042] Polyionic liquid synergist 0.1–0.5 parts

[0043] Antioxidant 0.5–1.5 parts

[0044] Light stabilizer 0.1 to 0.5 parts

[0045] Lubricant 0.1 to 0.5 parts

[0046] 1-3 parts of coloring masterbatch

[0047] The polyionic liquid synergist includes one or more of the following: quaternary ammonium dihydrogen phosphate polyionic liquid, imidazole dihydrogen phosphate polyionic liquid, and pyridine dihydrogen phosphate polyionic liquid.

[0048] Step 2, Mixed Extrusion: Mix and extrude the prepared raw materials.

[0049] The mixing extrusion step may include:

[0050] (a) The polyamide, the flame retardant, the polyionic liquid synergist, the antioxidant, the light stabilizer, the lubricant and the coloring masterbatch are premixed to form a uniform premix;

[0051] (b) The premixed material is fed to the main feed port of the twin-screw extruder via a loss-in-weight feeding system;

[0052] (c) During the extrusion process, the chopped glass fibers are introduced into the base and melting section by a side-feeding device;

[0053] (d) The polyamide material modified by the polyionic liquid is obtained by melt blending, extrusion, cooling, traction and pelletizing at a processing temperature of 280℃~320℃.

[0054] Another aspect of the present invention provides a polyamide material modified with a polyionic liquid prepared by the above method.

[0055] Another aspect of the present invention provides the application of polyionic liquid-modified polyamide materials in new energy vehicle components, wherein the components include:

[0056] (a) Insulation and flame-retardant components of the electric drive system;

[0057] (b) Flame-retardant protective structure of the battery module;

[0058] (c) High-temperature resistant packaging components of the electronic control unit;

[0059] (d) Coolant-resistant and oil-resistant components of the vehicle thermal management system.

[0060] Beneficial effects

[0061] The polyionic liquid-modified low-emission V0 flame-retardant high-temperature polyamide material of this invention meets the following requirements: a) It meets the V0 flame-retardant requirements for UL 94 from 0.4 mm to 3.2 mm; b) In aging tests at 23-85°C, relative humidity (RH) of 50-85%, and for 1000 hours, the amount of flame retardant released is less than 0.25 wt%, meeting the requirements for high gloss of the product; c) Excellent resistance to coolant (ethylene glycol aqueous solution), with the tensile strength retention rate of the material above 85% and the elongation at break above 90% under aging conditions of 3000 hours at 130°C in coolant; d) Excellent resistance to oil (transmission oil, IDEMITSU EDF 03), with the tensile strength retention rate of the material above 95%, the elongation at break above 90%, and the CTI retention rate above 100% under aging conditions of 504 hours at 150°C in transmission oil. Detailed Implementation

[0062] The products and methods of the present invention will be described in more detail below. The present invention is not limited to the following specific embodiments, and other features and advantages of the inventive concept will become apparent from the following specific embodiments.

[0063] Regarding terminology definitions, unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art. In case of conflict, this document (including the definitions) shall prevail. Preferred methods and materials are described below, but similar or equivalent methods and materials may also be used in the practice or testing of the invention. The materials, methods, and examples disclosed herein are illustrative only and not intended to be limiting.

[0064] As used herein, the terms “comprising,” “including,” “having,” “having,” “may,” “containing,” and variations thereof are intended to refer to open transitional phrases, terms, or words that do not exclude the presence or addition of one or more additional features, steps, operations, elements, or components. Unless the context explicitly indicates otherwise, objects without quantifiers include plural objects. However, whether explicitly stated or not, this disclosure also includes other embodiments that “include the embodiments or elements shown herein,” “consist of the embodiments or elements shown herein,” and “consist substantially of the embodiments or elements shown herein.”

[0065] Any range given in absolute or approximate terms is intended to include both, and any definitions used herein are intended to be illustrative rather than limiting. While the numerical ranges and parameters stating a wide range of the invention are approximate, the numerical values ​​stated in the specific embodiments are as precise as possible. However, any numerical value inherently includes some error that must be caused by the standard deviation found in the measurements of the respective tests. Furthermore, all ranges disclosed herein are to be understood to include any and all subranges (including all fractions and integers) included therein.

[0066] All ranges and parameters disclosed herein should be understood to encompass any and all subranges contained therein, and every number between the endpoints. For example, the specified range “1 to 10” should be considered to include any and all subranges between (and including) the minimum value of 1 and the maximum value of 10; that is, all subranges that begin with a minimum value of 1 or greater (e.g., 1 to 6.1) and end with a maximum value of 10 or less (e.g., 2.3 to 9.4, 3 to 8, 4 to 7), and finally the individual numbers 1, 2, 3, 4, 5, 6, 7, 8, 9, and 10 contained within that range. Unless otherwise stated, all percentages, ratios, and proportions herein are by weight.

[0067] Furthermore, this invention includes any and all possible combinations of some or all of the various embodiments described herein. Any and all documents referenced in this application are incorporated herein by reference in their entirety.

[0068] According to one embodiment of this application, a polyionic liquid-modified polyamide material may comprise, based on a total of 100 parts by weight, the following components in parts by weight:

[0069] 35-60 parts of polyamide

[0070] 20-50 parts chopped glass fiber

[0071] 10-30 parts flame retardant

[0072] Polyionic liquid synergist 0.1-2 parts

[0073] Antioxidant 0.1 to 1 part

[0074] Light stabilizer 0.1 to 1 part

[0075] Lubricant 0.1 to 0.5 parts

[0076] 1-5 parts of coloring masterbatch

[0077] The polyionic liquid synergist includes one or more of the following: quaternary ammonium dihydrogen phosphate polyionic liquid, imidazole dihydrogen phosphate polyionic liquid, and pyridine dihydrogen phosphate polyionic liquid.

[0078] According to one embodiment of this application, the preferred polyamide may comprise one or more of PA6T / 66, PA6T / 8T / 66, PA6I / 6T, PA6T / 6I, PA9T, and PA10T, with an Ubbelohde relative viscosity of 120–140 cm⁻¹. 3 / g (using concentrated sulfuric acid as solvent), preferably 120-130cm 3 / g (concentrated sulfuric acid as solvent).

[0079] According to one embodiment of this application, the polyamide may more preferably include one or more of PA6T / 66, PA6T / 6I, PA9T, and PA10T, and the Ubbelohde relative viscosity is preferably 120-130 cm⁻¹. 3 / g (concentrated sulfuric acid as solvent).

[0080] According to one embodiment of this application, the polyamide may further preferably include one or a mixture of two selected from PA6T / 66 and PA6T / 6I.

[0081] According to one embodiment of this application, the most preferred polyamide may include PA6T / 66.

[0082] According to one embodiment of this application, based on 100 parts by weight of polyamide material, the polyamide can be 35 to 60 parts. Alternatively, based on 100 parts by weight of polyamide material, the polyamide can be 40 to 55 parts, preferably 45 to 50 parts, and more preferably 46 to 48 parts.

[0083] According to one embodiment of this application, based on 100 parts by weight of polyamide material, the polyamide can be 35 to 60 parts of PA6T / 66, preferably 40 to 55 parts of PA6T / 66, more preferably 45 to 50 parts of PA6T / 66, and even more preferably 46 to 48 parts of PA6T / 66.

[0084] According to one embodiment of this application, the length of the chopped glass fiber can be 3–4.5 mm, preferably 3.5–4.5 mm, more preferably 4–4.5 mm. According to one embodiment of this application, the diameter of the chopped glass fiber can be 7–17 μm, preferably 8.5–17 μm. According to one embodiment of this application, the cross-section of the chopped glass fiber can be circular and / or elliptical. According to one embodiment of this application, the cross-section of the chopped glass fiber can be elliptical, and the ratio of the shorter to longer diameter of the ellipse can be 1:3 to 1:5.

[0085] According to one embodiment of this application, the length of the chopped glass fiber can be 3.5–4.5 mm, and the diameter can be 7–17 μm. Preferably, the length of the chopped glass fiber can be 4–4.5 mm, and the diameter can be 8.5–17 μm.

[0086] According to one embodiment of this application, the length of the chopped glass fiber can be 3.5–4.5 mm, and the diameter can be 7–17 μm. According to another embodiment of this application, the length of the chopped glass fiber can be 3–4.5 mm, the diameter can be 7–17 μm, and the cross-section can be circular and / or elliptical.

[0087] According to one embodiment of this application, the length of the chopped glass fiber can be 3–4.5 mm, the diameter can be 7–17 μm, and the cross-section can be elliptical, with the ratio of the shorter to the longer diameter of the ellipse being 1:3 to 1:5. According to another embodiment of this application, the length of the chopped glass fiber can be 4–4.5 mm, the diameter can be 8.5–17 μm, and the cross-section can be elliptical, with the ratio of the shorter to the longer diameter of the ellipse being 1:3 to 1:5.

[0088] According to one embodiment of this application, based on 100 parts by weight of polyamide material, the chopped glass fiber can be 20 to 50 parts. Furthermore, based on 100 parts by weight of polyamide material, the chopped glass fiber can be 22 to 45 parts, for example 24 to 40 parts, preferably 25 to 35 parts, more preferably 26 to 32 parts, and even more preferably 28 to 30 parts.

[0089] According to one embodiment of this application, the flame retardant may include a selection from CM3004, Exollt, etc. ® OP1230 and Exollt ® One or more of OP1400. Preferably, the flame retardant may include those selected from Exollt. ® OP1230 and Exollt ® One or more of OP1400. More preferably, the flame retardant may be Exollt. ® OP1230.

[0090] According to one embodiment of this application, the flame retardant can be 10 to 30 parts per 100 parts by weight of polyamide material. Furthermore, the flame retardant can be 12 to 25 parts per 100 parts by weight of polyamide material, preferably 14 to 20 parts, and more preferably 16 to 18 parts.

[0091] According to one embodiment of this application, the polyionic liquid synergist may include an ionic liquid polymer with synergistic flame retardant function.

[0092] According to one embodiment of this application, the polyionic liquid synergist may include one or more of the following: quaternary ammonium dihydrogen phosphate polyionic liquid, imidazole dihydrogen phosphate polyionic liquid, and pyridine dihydrogen phosphate polyionic liquid.

[0093] According to one embodiment of this application, a quaternary ammonium dihydrogen phosphate polyionic liquid can be formed from a quaternary ammonium dihydrogen phosphate monomer of formula a:

[0094] Formula a

[0095]

[0096] Wherein, R1 can be an alkyl group and R2 can be an alkylene group.

[0097] In formula a, R1 can be a C1-C30 alkyl group, preferably a C1-C20 alkyl group, more preferably a C1-C10 alkyl group, and even more preferably a C2-C6 alkyl group. For example, R1 can be methyl, ethyl, propyl, butyl, pentyl, hexyl, heptyl, octyl, nonyl, or decyl. Preferably, R1 can be methyl, ethyl, propyl, butyl, pentyl, or hexyl. More preferably, R1 can be ethyl, butyl, or hexyl. For example, R1 can be ethyl, n-butyl, or n-hexyl.

[0098] In formula a, R2 can be a C1-C30 alkylene group, preferably a C1-C20 alkylene group, more preferably a C1-C10 alkylene group, and even more preferably a C2-C6 alkylene group. For example, R2 can be methylene, ethylene, propylene, butylene, pentylene, hexylene, heptylene, octylene, nonylene, or decylene. Preferably, R2 can be methylene, ethylene, propylene, butylene, pentylene, or hexylene. More preferably, R2 can be ethylene, butylene, or hexylene. For example, R2 can be ethylene, n-butylene, or n-hexylene.

[0099] Furthermore, in equation a, R2 can be -(CH2). n - where n is an integer from 1 to 30, preferably an integer from 1 to 20, more preferably an integer from 1 to 10, and even more preferably an integer from 2 to 6. For example, R2 can be -(CH2)2-, -(CH2)4-, or -(CH2)6-.

[0100] According to one embodiment of this application, the imidazole-type dihydrogen phosphate polyionic liquid is formed from an imidazole-type dihydrogen phosphate monomer of formula b:

[0101] Formula b

[0102]

[0103] R3 can be an alkyl group, and R4 can be an alkylene group.

[0104] In formula b, R3 can be a C1-C30 alkyl group, preferably a C1-C20 alkyl group, more preferably a C1-C10 alkyl group, and even more preferably a C2-C6 alkyl group. For example, R3 can be methyl, ethyl, propyl, butyl, pentyl, hexyl, heptyl, octyl, nonyl, or decyl. Preferably, R3 can be methyl, ethyl, propyl, butyl, pentyl, or hexyl. More preferably, R3 can be methyl.

[0105] In formula b, R4 can be a C1-C30 alkylene group, preferably a C1-C20 alkylene group, more preferably a C1-C10 alkylene group, and even more preferably a C2-C6 alkylene group. For example, R4 can be methylene, ethylene, propylene, butylene, pentylene, hexylene, heptylene, octylene, nonylene, or decylene. Preferably, R4 can be methylene, ethylene, propylene, butylene, pentylene, or hexylene. More preferably, R4 can be ethylene, butylene, or hexylene. For example, R4 can be ethylene, n-butylene, or n-hexylene.

[0106] Furthermore, in equation b, R4 can be -(CH2). n - where n is an integer from 1 to 30, preferably an integer from 1 to 20, more preferably an integer from 1 to 10, and even more preferably an integer from 2 to 6. For example, R4 can be -(CH2)2-, -(CH2)4-, or -(CH2)6-.

[0107] According to one embodiment of this application, the pyridine-type dihydrogen phosphate polyionic liquid is formed from a pyridine-type dihydrogen phosphate monomer of formula c below:

[0108] Formula c

[0109]

[0110] R5 is an alkylene group.

[0111] In formula c, R5 can be a C1-C30 alkylene group, preferably a C1-C20 alkylene group, more preferably a C1-C10 alkylene group, and even more preferably a C2-C6 alkylene group. For example, R5 can be methylene, ethylene, propylene, butylene, pentylene, hexylene, heptylene, octylene, nonylene, or decylene. Preferably, R5 can be methylene, ethylene, propylene, butylene, pentylene, or hexylene. More preferably, R5 can be ethylene, butylene, or hexylene. For example, R5 can be ethylene, n-butylene, or n-hexylene.

[0112] Furthermore, in equation c, R5 can be -(CH2). n- where n is an integer from 1 to 30, preferably an integer from 1 to 20, more preferably an integer from 1 to 10, and even more preferably an integer from 2 to 6. For example, R5 can be -(CH2)2-, -(CH2)4-, or -(CH2)6-.

[0113] According to one embodiment of this application, the polyionic liquid synergist can be 0.1 to 2 parts per 100 parts by weight of polyamide material. Furthermore, the polyionic liquid synergist can be 0.2 to 1.8 parts per 100 parts by weight of polyamide material, preferably 0.4 to 1.6 parts, more preferably 0.5 to 1.5 parts, and even more preferably 0.8 to 1.2 parts. For example, the polyionic liquid synergist can be 1 part per 100 parts by weight of polyamide material.

[0114] In addition to the polyionic liquid synergists mentioned above, suitable polyionic liquid synergists can be selected according to the actual material performance requirements, such as polyionic liquids with other alkyl chain lengths.

[0115] According to one embodiment of this application, the antioxidant may include one or more selected primary and secondary antioxidants. Preferably, the weight ratio of the primary antioxidant to the secondary antioxidant is 1:1 to 10:1, more preferably 1:1 to 5:1, more preferably 1:1 to 4:1, even more preferably 1:1 to 3:1, even more preferably 1:1 to 2:1, and even more preferably 1:1 to 1.5:1. For example, the weight ratio of the primary antioxidant to the secondary antioxidant may be 1.3:1 to 1.5:1.

[0116] According to one embodiment of this application, the primary antioxidant preferably includes a hindered phenolic antioxidant. According to one embodiment of this application, the secondary antioxidant preferably includes a phosphite antioxidant. Preferably, the hindered phenolic antioxidant may include those selected from RIANOX. ® 1098: N,N'-hexamethylenebis(3,5-di-tert-butyl-4-hydroxyphenylpropionamide) and RIANOX ® 1010: One or more of pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionic acid]. Preferably, the phosphite antioxidant may include those selected from RIANOX. ® 686: Bis(2,4-dicumylphenyl)pentaerythritol diphosphite and RIANOX ® 168: One or more of tris(2,4-di-tert-butylphenyl) phosphite.

[0117] According to one embodiment of this application, the antioxidant can be 0.1 to 1 part per 100 parts by weight of polyamide material. Furthermore, the antioxidant can be 0.15 to 0.5 parts per 100 parts by weight of polyamide material, for example 0.2 to 0.45 parts, preferably 0.25 to 0.4 parts, and more preferably 0.3 to 0.35 parts.

[0118] According to one embodiment of this application, based on 100 parts by weight of polyamide material, the main antioxidant hindered phenolic antioxidant can be 0.05 to 0.5 parts, for example 0.1 to 0.45 parts, preferably 0.15 to 0.4 parts, more preferably 0.16 to 0.35 parts, particularly preferably 0.18 to 0.3 parts, for example 0.2 to 0.25 parts.

[0119] According to one embodiment of this application, based on 100 parts by weight of polyamide material, the auxiliary antioxidant phosphite antioxidant can be 0.05 to 0.5 parts, for example 0.06 to 0.45 parts, preferably 0.08 to 0.4 parts, more preferably 0.1 to 0.35 parts, particularly preferably 0.12 to 0.3 parts, for example 0.15 to 0.2 parts.

[0120] According to one embodiment of this application, based on 100 parts by weight of polyamide material, the total amount of primary antioxidant and secondary antioxidant can be 0.1 to 1 part. For example, based on 100 parts by weight of polyamide material, the total amount of primary antioxidant and secondary antioxidant can be 0.15 to 0.5 parts, for example 0.2 to 0.45 parts, preferably 0.25 to 0.4 parts, and more preferably 0.3 to 0.35 parts.

[0121] According to one embodiment of this application, the light stabilizer can be a hindered amine light stabilizer. Preferably, the hindered amine light stabilizer includes one or more selected from N,N'-bis(2,2,6,6-tetramethyl-4-piperidinyl)-N,N'-dialdehyde hexamethylenediamine and bis(2,2,6,6-tetramethyl-4-piperidinyl) sebacate. More preferably, the hindered amine light stabilizer is N,N'-bis(2,2,6,6-tetramethyl-4-piperidinyl)-N,N'-dialdehyde hexamethylenediamine.

[0122] According to one embodiment of this application, the light stabilizer can be 0.1 to 1 part per 100 parts by weight of polyamide material. Furthermore, the light stabilizer can be 0.2 to 0.8 parts per 100 parts by weight of polyamide material, preferably 0.3 to 0.6 parts, and more preferably 0.4 to 0.5 parts.

[0123] According to one embodiment of this application, the lubricant may include one or more selected from stearates and polymeric ionic liquid complexes. Preferably, the stearates may include one or more selected from calcium stearate, magnesium stearate, and zinc stearate. Preferably, the polyionic liquid complex may include one or more selected from F-S2500 complex and AF-25 complex. More preferably, the lubricant may include one or more selected from magnesium stearate, zinc stearate, and F-S2500 complex.

[0124] According to one embodiment of this application, the lubricant can be 0.1 to 0.5 parts per 100 parts by weight of polyamide material. Furthermore, the lubricant can be 0.15 to 0.4 parts per 100 parts by weight of polyamide material, preferably 0.2 to 0.35 parts, and more preferably 0.25 to 0.3 parts.

[0125] According to one embodiment of this application, the coloring masterbatch includes one or more selected from carbon black masterbatch and orange masterbatch.

[0126] According to one embodiment of this application, the coloring masterbatch may include at least one selected from high-pigment carbon black masterbatch, custom orange masterbatch RAL 2003, RAL 2004, and RAL 2009. Preferably, the coloring masterbatch may include high-pigment carbon black masterbatch.

[0127] According to one embodiment of this application, the coloring masterbatch can be 1 to 5 parts per 100 parts by weight of polyamide material. Furthermore, the coloring masterbatch can be 1.5 to 4 parts per 100 parts by weight of polyamide material, more preferably 2 to 3 parts.

[0128] According to one embodiment of this application, the UL94 flame retardancy rating of polyamide materials from 0.4 mm to 3.2 mm can be V0. Specifically, the UL94 flame retardancy rating of polyamide materials from 0.4 mm to 0.8 mm can be V0, the UL94 flame retardancy rating of polyamide materials from 1.6 mm to 3.2 mm can be V0.

[0129] According to one embodiment of this application, the amount of flame retardant released (expressed as the weight fraction of phosphorus (P)) in the polyamide material during an aging test at 23–85°C, 50–85% relative humidity, and 1000 hours is 0.25 wt% or less. Specifically, the amount of flame retardant released (expressed as the weight fraction of phosphorus (P)) in the polyamide material during an aging test at 23°C, 50% relative humidity, and 1000 hours is 0.25 wt% or less, preferably 0.24 wt% or less, more preferably 0.23 wt% or less. The amount of flame retardant released (expressed as the weight fraction of phosphorus (P)) in the polyamide material during an aging test at 60°C, 72% relative humidity, and 1000 hours is 0.25 wt% or less, preferably 0.24 wt% or less. The amount of flame retardant released (expressed as the weight fraction of phosphorus (P)) in the aging test of polyamide material at 85°C, 85% relative humidity and 1000 hours is less than 0.25 wt%, preferably less than 0.24 wt%.

[0130] According to one embodiment of this application, the polyamide material retains more than 85% of its tensile strength and more than 90% of its elongation at break under the conditions of 3000 hours in a coolant (ethylene glycol aqueous solution) and 130°C.

[0131] According to one embodiment of this application, the polyamide material retains more than 95% of its tensile strength, more than 90% of its elongation at break, and 100% of its CTI under aging conditions of 504 hours and 150°C in transmission fluid (IDEMITSU EDF 03). Furthermore, the transmission fluid is not limited to IDEMITSU EDF 03; other commonly used transmission fluids in the art, such as FUCHS4101 and Castrol BOT395, can also be used.

[0132] The polyionic liquid-modified polyamide material of the present invention can be prepared by the following method, including the following steps:

[0133] Step 1: Prepare raw materials: including the aforementioned components and their respective weight proportions.

[0134] Step 2, Twin-screw mixing extrusion: Mix and extrude the prepared raw materials.

[0135] According to one embodiment of this application, the above-mentioned mixed extrusion step is as follows:

[0136] (a) Polyamide, flame retardant, polyionic liquid synergist, antioxidant, light stabilizer, lubricant and color masterbatch are premixed to form a homogeneous premix;

[0137] (b) The premix is ​​fed to the main feed port of the twin-screw extruder via a loss-in-weight feeding system;

[0138] (c) During the extrusion process, chopped glass fibers are introduced into the base and melting section via a side-feeding device;

[0139] (d) The polyamide material modified by polyionic liquid was obtained by melt blending, extrusion, cooling, drawing and pelletizing at a processing temperature of 280℃~320℃.

[0140] According to one embodiment of this application, in the above-mentioned mixing extrusion step, the extrusion temperature can be, for example, 280°C, 285°C, 290°C, 295°C, 300°C, 305°C, 310°C, or 320°C.

[0141] The above description of the components (including content) in polyionic liquid modified polyamide materials applies to the components (including content) in the preparation method.

[0142] The polyamide material modified by the polyionic liquid of this invention can be applied to key components of new energy vehicles, and specific application scenarios include, but are not limited to:

[0143] (a) Insulation and flame-retardant components of the electric drive system;

[0144] (b) Flame-retardant protective structure of the battery module;

[0145] (c) High-temperature resistant packaging components of the electronic control unit;

[0146] (d) Coolant-resistant and oil-resistant components of the vehicle thermal management system.

[0147] Example

[0148] The technical solution of the present invention will be described in more detail below with reference to specific comparative examples and embodiments. The above content can be better understood by referring to the following embodiments, but the embodiments are intended to be illustrative and not to limit the scope of the invention. In particular, the embodiments illustrate representative embodiments of the inherent principles of the invention, and these principles are not strictly limited to the specific conditions described in these embodiments. Therefore, it should be understood that the present invention covers various changes and modifications to the embodiments described herein, and such changes and modifications can be made without departing from the spirit and scope of the invention and without diminishing its intended advantages. Therefore, such changes and modifications are contemplated to be included in the appended claims.

[0149] Comparative Example 1

[0150] The ordinary polyamide material 1 in this comparative example is composed of the following components in parts by weight: 47 parts polyamide PA6T / 66 (E430NT5), 30 parts chopped glass fiber (T435TM), 20 parts flame retardant (CM3004), and 0.25 parts hindered phenolic antioxidant (RIANOX). ®1098), 0.15 parts of phosphite antioxidant (RIANOX) ® 686), 0.35 parts light stabilizer (RIASORB) ® UV-944), 0.25 parts lubricant (CMS P-130), and 2 parts carbon black masterbatch.

[0151] The preparation method of the ordinary polyamide material 1 in Comparative Example 1 includes the following steps:

[0152] Step 1: Mix polyamide PA6T / 66, flame retardant, antioxidant, light stabilizer, lubricant, and carbon black masterbatch until homogeneous.

[0153] Step 2: Add the mixture obtained in Step 1 into a twin-screw extruder. The twin-screw extruder has a total of 9 temperature sections. The temperature of the first and second sections is 280 degrees Celsius, and the temperature of the other three sections is 310 degrees Celsius. The main machine speed is 800 rpm. Short glass fibers are added from the side feed during the extrusion process. Finally, after extrusion, cooling, traction, and pelletizing, the polyamide composite material is obtained.

[0154] The obtained material was dried at 100 degrees Celsius for 6 hours in a dehumidifying dryer, and then injection molded into test samples.

[0155] Comparative Example 2

[0156] The ordinary amide material 2 in this comparative example is composed of the following components in parts by weight: 47 parts polyamide PA6T / 66 (E430NT5), 30 parts chopped glass fiber (T435TM), and 20 parts flame retardant (Exollt). ® OP1230), 0.25 parts hindered phenolic antioxidant (RIANOX) ® 1098), 0.15 parts of phosphite antioxidant (RIANOX) ® 686), 0.35 parts light stabilizer (RIASORB) ® UV-944), 0.25 parts lubricant (CMS P-130), and 2 parts carbon black masterbatch.

[0157] The preparation method of ordinary polyamide material 2 in this comparative example is the same as that in comparative example 1.

[0158] Comparative Example 3

[0159] The ordinary polyamide material 3 in this comparative example is composed of the following components in parts by weight: 47 parts polyamide PA6T / 66 (E430NT5), 30 parts chopped glass fiber (T435TM), and 20 parts flame retardant (Exollt). ® OP1400), 0.25 parts hindered phenolic antioxidant (RIANOX) ®1098), 0.15 parts of phosphite antioxidant (RIANOX) ® 686), 0.35 parts light stabilizer (RIASORB) ® UV-944), 0.25 parts lubricant (CMS P-130), and 2 parts carbon black masterbatch.

[0160] The preparation method of ordinary polyamide material 3 in this comparative example is the same as that in comparative example 1.

[0161] Example 1

[0162] The polyionic liquid-modified low-emission V0 flame-retardant high-temperature polyamide material 1 of this embodiment is composed of the following components in parts by weight: 48 parts polyamide PA6T / 66 (E430NT5), 30 parts chopped glass fiber (T435TM), 18 parts flame retardant OP1230, 1.0 part polyionic liquid synergist (quaternary ammonium dihydrogen phosphate polyionic liquid, wherein R1 in monomer a is butyl and R2 is n-butylene), and 0.2 parts hindered phenolic antioxidant (RIANOX). ® 1098), 0.15 parts of phosphite antioxidant (RIANOX) ® 686), 0.4 parts light stabilizer (RIASORB) ® UV-944), 0.25 parts lubricant (CMS P-130), and 2 parts carbon black masterbatch.

[0163] The preparation method of the polyionic liquid modified low-precipitation V0 flame-retardant high-temperature polyamide material 1 in this embodiment is the same as that in comparative example 1.

[0164] Example 2

[0165] The polyionic liquid modified low-emission V0 flame-retardant high-temperature polyamide material 2 of this embodiment is composed of the following components in parts by weight: 48 parts polyamide PA6T / 66 (E430NT5), 30 parts chopped glass fiber (T435TM), 18 parts flame retardant OP1230, 1.0 part polyionic liquid synergist (imidazolium dihydrogen phosphate polyionic liquid, wherein R3 in monomer formula b is methyl and R4 is n-butylene), and 0.2 parts hindered phenolic antioxidant (RIANOX). ® 1098), 0.15 parts of phosphite antioxidant (RIANOX) ® 686), 0.4 parts light stabilizer (RIASORB) ® UV-944), 0.25 parts lubricant (CMS P-130), and 2 parts carbon black masterbatch.

[0166] The preparation method of the polyionic liquid modified low-precipitation V0 flame-retardant high-temperature polyamide material 2 in this embodiment is the same as that in comparative example one.

[0167] Example 3

[0168] The polyionic liquid-modified low-emission V0 flame-retardant high-temperature polyamide material 3 of this embodiment is composed of the following components in parts by weight: 48 parts polyamide PA6T / 66 (E430NT5), 30 parts chopped glass fiber (T435TM), 18 parts flame retardant OP1230, 1.0 part polyionic liquid synergist (pyridine-type dihydrogen phosphate polyionic liquid, wherein R5 in monomer c is n-butylene), and 0.2 parts hindered phenolic antioxidant (RIANOX). ® 1098), 0.15 parts of phosphite antioxidant (RIANOX) ® 686), 0.4 parts light stabilizer (RIASORB) ® UV-944), 0.25 parts lubricant (CMS P-130), and 2 parts carbon black masterbatch.

[0169] The preparation method of the polyionic liquid modified low-precipitation V0 flame-retardant high-temperature polyamide material 3 in this embodiment 3 is the same as that in comparative example 1.

[0170] Example 4

[0171] The polyionic liquid-modified low-emission V0 flame-retardant high-temperature polyamide material 4 of this embodiment is composed of the following components in parts by weight: 48 parts polyamide PA6T / 66 (E430NT5), 30 parts chopped glass fiber (T435TM), 18 parts flame retardant OP1230, 1.0 part polyionic liquid synergist (pyridine-type dihydrogen phosphate polyionic liquid, wherein R5 in monomer c is n-hexylene), and 0.2 parts hindered phenolic antioxidant (RIANOX). ® 1098), 0.15 parts of phosphite antioxidant (RIANOX) ® 686), 0.4 parts light stabilizer (RIASORB) ® UV-944), 0.25 parts lubricant (CMS P-130), and 2 parts carbon black masterbatch.

[0172] The preparation method of the polyionic liquid modified low-precipitation V0 flame-retardant high-temperature polyamide material 4 in this embodiment 4 is the same as that in comparative example 1.

[0173] Polyamide material performance testing

[0174] The properties of the materials obtained in the comparative examples and embodiments were tested and evaluated using the following methods:

[0175] 1) Aging oven: Memmert; Flame retardant testing equipment: ATLAS @ HVUL2; CTI: Proof Tracking Tester LDH

[0176] 2) EDS elemental analysis testing equipment: SEM JEOL JSM-IT200

[0177] 3) Universal tensile testing equipment: Zwick ® Z020

[0178] 4) Injection molded test specimens: 80 mm × 10 mm × 4 mm specimens, ISO 179 specimens; 170 mm × 20 mm × 2 mm specimens, ISO 179 1A specimens; UL94 flame retardant test specimens of 0.4 mm, 0.8 mm, 1.6 mm, and 3.2 mm.

[0179] 5) Flame retardant release test conditions include:

[0180] Condition 1: 23℃, 50% relative humidity, 1000 hours;

[0181] Condition 2: 60℃, 72% relative humidity, 1000 hours;

[0182] Condition 3: 85℃, 85% relative humidity, 1000 hours.

[0183] Coolant (G40, a 1:1 weight mixture of ethylene glycol and water) at 130°C for 3000 hours, with time selection nodes at 0 hours, 50 hours, 500 hours, 1000 hours, 2000 hours, and 3000 hours.

[0184] Transmission fluid (IDEMITSU EDF 03) 150℃, 504 hours, time selection nodes 0 hours, 168 hours, 336 hours, 504 hours.

[0185] The formulas for calculating the tensile strength retention rate and elongation at break retention rate are as follows, where tensile strength refers to the tensile strength at break:

[0186]

[0187]

[0188] The following table shows the performance test results of the polyamide materials in the comparative examples and embodiments:

[0189] Table 1: Flame retardant properties of UL 94 0.4 mm~3.2 mm

[0190]

[0191] Table 2: Elemental analysis of EDS released from flame retardants, weight fraction of phosphorus (P)

[0192]

[0193] Table 3: Results of tensile strength retention and elongation at break retention, aging in coolant (G40, ethylene glycol and water mixed in a 1:1 weight ratio), 130℃, 3000 hours.

[0194]

[0195] Table 4: Results of tensile strength retention and elongation at break retention, aging of transmission fluid (IDEMITSU EDF 03), 150℃, 504 hours.

[0196]

[0197] Table 5: CTI retention rate results, transmission fluid (IDEMITSU EDF 03) aging, 150℃, 504 hours

[0198]

[0199] Based on the test results in the table above, it can be seen that the polyionic liquid modified low-emission V0 flame-retardant high-temperature polyamide material of the present invention can achieve the following performance characteristics: a) UL 94 meets the V0 flame retardant requirements for sizes from 0.4 mm to 3.2 mm; b) In the aging test at 60°C, 72% relative humidity, and 1000 hours, the amount of flame retardant emission is less than 0.25 wt%, meeting the requirements for high gloss of the product; c) Excellent resistance to coolant (ethylene glycol aqueous solution), with tensile strength retention of over 85% and elongation at break of over 90% after 3000 hours at 130°C; d) Excellent resistance to oil (transmission oil, IDEMITSU EDF 03), with tensile strength retention of over 95%, elongation at break of over 90%, and CTI retention of 100% after 504 hours at 150°C.

[0200] This invention provides a high-performance polyionic liquid-modified, low-VOC, flame-retardant, high-temperature polyamide material by utilizing a novel polyionic liquid synergist that combines the functionality of an ionic liquid as a green solvent with the processing stability of polymers. The green solvent characteristics include: a) low volatility, near-zero VOCs (volatile organic compounds), conforming to green chemistry principles; b) high thermal and chemical stability; and c) recyclability, reducing environmental pollution. The novel polyionic liquid synergist of this invention exhibits excellent structural designability, for example, by: a) adjusting the cation (quaternary ammonium salt, imidazole, pyridine, etc.); b) designing anions (PF6). -(a) Phosphate, sulfonate); c) Introduce specific functional groups (flame retardant groups, hydrophobic segments, alkyl segments, etc.) through copolymerization or graft modification to precisely customize polyionic liquid synergists. Preferably, the advantages of polyionic liquid synergists include, but are not limited to, the following: a) Polarity matching high-temperature polyamides can improve the compatibility of modified polyamide systems. They have a special "intermolecular crosslinking" effect, which can be compounded with traditional nitrogen and phosphorus flame retardants to form a new flame retardant system. At the same time, it reduces the phase separation effect of the entire formulation system, reduces the amount of traditional flame retardants, and thus reduces the risk of small molecule flame retardant precipitation, achieving the 0.4 mm~3.2 mm V0 flame retardant requirements; b) The unique polymer structure of polyionic liquids can anchor the precipitation risk of small molecule flame retardants and reduce the accumulation of mold fouling after material injection molding; c) By adjusting the alkyl chain length, the mechanical properties of the material can be improved.

[0201] Although the invention can be embodied in many different forms, specific preferred embodiments of the invention are described in detail herein. This disclosure is an example of the principles of the invention and is not intended to limit the invention to the specific embodiments described. Furthermore, the invention covers any possible combination of some or all of the various embodiments mentioned herein, described herein, and / or incorporated herein. In addition, the invention also specifically excludes any possible combination of any or some of the various embodiments mentioned herein, described herein, and / or incorporated herein.

[0202] The foregoing disclosure is intended to be illustrative and not exhaustive. Individual elements or features of a particular embodiment are generally not limited to that particular embodiment, but may be used in other embodiments and may be combined in other ways, even if not specifically shown or described. Such variations are included in this invention. Based on the description herein, many modifications and alternatives will be conceived by those skilled in the art. All such alternatives and modifications are intended to be included within the scope of the claims. Those skilled in the art will recognize other equivalents of the specific embodiments described herein, which are also intended to be covered by the claims.

Claims

1. A polyamide material modified with a polyionic liquid, comprising, based on 100 parts by weight, the following components in parts by weight: 35-60 parts of polyamide 20-50 parts chopped glass fiber 10-30 parts flame retardant Polyionic liquid synergist 0.1-2 parts Antioxidant 0.1 to 1 part Light stabilizer 0.1 to 1 part Lubricant 0.1 to 0.5 parts 1-5 parts of coloring masterbatch in, The polyionic liquid synergist includes one or more of the following: quaternary ammonium dihydrogen phosphate polyionic liquid, imidazole dihydrogen phosphate polyionic liquid, and pyridine dihydrogen phosphate polyionic liquid.

2. The polyamide material modified with polyionic liquid according to claim 1, wherein the polyamide comprises one or more of PA6T / 66, PA6T / 8T / 66, PA6I / 6T, PA6T / 6I, PA9T, and PA10T, and the polyamide has an Ubbelohde relative viscosity of 120-140 cm⁻¹ using concentrated sulfuric acid as the test solvent. 3 / g.

3. The polyamide material modified by ionic liquid according to claim 1, wherein the chopped glass fibers have a length of 3.0 to 4.5 mm and a diameter of 11 to 17 μm.

4. The polyamide material modified by polyionic liquid according to claim 1, wherein the chopped glass fibers have a length of 3.0 to 4.5 mm, a diameter of 11 to 17 μm, and a circular and / or elliptical cross-section.

5. The polyamide material modified by polyionic liquid according to claim 1, wherein the chopped glass fiber has a length of 3.0 to 4.5 mm, a diameter of 11 to 17 μm, and an elliptical cross-section, wherein the ratio of the short and long diameters of the ellipse is 1:3 to 1:

5.

6. The polyamide material modified with polyionic liquid according to claim 1, wherein the flame retardant comprises flame retardant selected from Exollt. ® OP1230 and flame retardant Exollt ® One or more of OP1400.

7. The polyamide material modified with a polyionic liquid according to claim 1, wherein the quaternary ammonium dihydrogen phosphate polyionic liquid is formed from a quaternary ammonium dihydrogen phosphate monomer of formula a: Formula a , in, R1 is an alkyl group, and R2 is an alkylene group.

8. The polyamide material modified by polyionic liquid according to claim 7, wherein R2 is ethylidene, n-butylidene, or n-hexylidene.

9. The polyionic liquid-modified polyamide material according to claim 1, wherein the imidazole-type dihydrogen phosphate polyionic liquid is formed from an imidazole-type dihydrogen phosphate monomer of formula b: Formula b , R3 is an alkyl group and R4 is an alkylene group.

10. The polyamide material modified by the polyionic liquid according to claim 9, wherein R4 is ethylidene, n-butylidene, or n-hexylidene.

11. The polyionic liquid-modified polyamide material according to claim 1, wherein the pyridine-type dihydrogen phosphate polyionic liquid is formed from a pyridine-type dihydrogen phosphate monomer of formula c: Formula c , in, R5 is an alkylene group.

12. The polyamide material modified by polyionic liquid according to claim 11, wherein R5 is ethylidene, n-butylidene, or n-hexylidene.

13. The polyamide material modified with polyionic liquid according to claim 1, wherein the antioxidant comprises one or more selected from hindered phenolic antioxidants and phosphite antioxidants, wherein the hindered phenolic antioxidant comprises one or more selected from N,N'-hexamethylene bis(3,5-di-tert-butyl-4-hydroxyphenylpropionamide) and pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate]; and the phosphite antioxidant comprises one or more selected from bis(2,4-dicumylphenyl)pentaerythritol diphosphite and tris(2,4-di-tert-butylphenyl) phosphite.

14. The polyamide material modified by polyionic liquid according to claim 1, wherein the light stabilizer comprises one or more selected from N,N'-bis(2,2,6,6-tetramethyl-4-piperidinyl)-N,N'-dialdehyde hexamethylenediamine and bis(2,2,6,6-tetramethyl-4-piperidinyl) sebacate.

15. The polyamide material modified by polyionic liquid according to claim 1, wherein the lubricant comprises one or more selected from polymeric ionic liquid complexes and stearates, wherein the stearates comprise one or more selected from calcium stearate, magnesium stearate and zinc stearate.

16. The polyionic liquid modified polyamide material according to claim 1, wherein the coloring masterbatch comprises one or more selected from carbon black masterbatch and orange masterbatch.

17. The polyamide material modified by the polyionic liquid according to claim 1, wherein the UL940.4 mm to 3.2 mm flame retardancy rating of the polyamide material is V0.

18. The polyamide material modified by polyionic liquid according to claim 1, wherein the amount of flame retardant released in the aging test of the polyamide material under the conditions of 23~85°C, 50~85% relative humidity and 1000 hours is less than 0.25 wt%, wherein the amount of flame retardant released is expressed as the weight fraction of phosphorus.

19. The polyamide material modified by ionic liquid according to claim 1, wherein the polyamide material retains a tensile strength of more than 85% and an elongation at break of more than 90% under aging conditions of 3000 hours in ethylene glycol aqueous solution and 130°C.

20. The polyamide material modified by the polyionic liquid according to claim 1, wherein the polyamide material retains more than 95% of its tensile strength, more than 90% of its elongation at break, and 100% of its relative tracking index under the aging conditions of 504 hours and 150°C in transmission oil.

21. A method for preparing a polyamide material modified by a polyionic liquid, comprising the following steps: Step 1, Prepare raw materials: The raw materials consist of the following components in parts by weight based on a total of 100 parts by weight: 35-60 parts of polyamide 20-50 parts chopped glass fiber 10-30 parts flame retardant Polyionic liquid synergist 0.1-2 parts Antioxidant 0.1 to 1 part Light stabilizer 0.1 to 1 part Lubricant 0.1 to 0.5 parts 1-5 parts of coloring masterbatch in, The polyionic liquid synergist includes one or more selected from the following: quaternary ammonium dihydrogen phosphate polyionic liquids, imidazole dihydrogen phosphate polyionic liquids, and pyridine dihydrogen phosphate polyionic liquids. Step 2, Mixed Extrusion: Mix and extrude the prepared raw materials.

22. The preparation method according to claim 21, wherein the mixing extrusion step comprises: (a) The polyamide, the flame retardant, the polyionic liquid synergist, the antioxidant, the light stabilizer, the lubricant and the coloring masterbatch are premixed to form a uniform premix; (b) The premixed material is fed to the main feed port of the twin-screw extruder via a loss-in-weight feeding system; (c) During the extrusion process, the chopped glass fibers are introduced into the base and melting section by a side-feeding device; (d) The polyamide material modified by the polyionic liquid is obtained by melt blending, extrusion, cooling, traction and pelletizing at a processing temperature of 280℃~320℃.

23. A polyamide material modified by a polyionic liquid, which is prepared by the method according to claim 21 or 22.

24. The application of the polyionic liquid-modified polyamide material according to any one of claims 1 to 20 and 23, or the polyionic liquid-modified polyamide material prepared by the preparation method according to claim 21 or 22, in new energy vehicle components, wherein, The component includes: (a) Insulation and flame-retardant components of the electric drive system; (b) Flame-retardant protective structure of the battery module; (c) High-temperature resistant packaging components of the electronic control unit; (d) Coolant-resistant and oil-resistant components of the vehicle thermal management system.

Citation Information

Patent Citations

  • A low-fouling, halogen-free, flame-retardant reinforced nylon material, its preparation method, and its application.

    CN115746556B

Cited By

  • Laser-weldable halogen-free V0 flame-retardant polyamide composite material and preparation method thereof

    CN120737598A